2019
DOI: 10.1002/ejoc.201900118
|View full text |Cite
|
Sign up to set email alerts
|

Gold and TfOH‐Cocatalyzed Tandem Reaction of ortho‐Akynylarylaldehydes with Cyclopropenes: an Efficient Route to Functionalized Benzo[7]annulene Derivatives

Abstract: A novel gold(III) and TfOH‐cocatalyzed reaction of ortho‐alkynylbenzaldehydes with cyclopropenes was described for the synthesis of a variety of functionalized benzo[7]annulene derivatives in a highly stereoselective manner. This reaction could undergo tandem [4+2] cycloaddition/ring expansion to achieve the construction of seven‐membered‐carbocycles, along with the cleavage of double bond of cyclopropenes. The reaction features simple operations, commercially available catalysts and broad substrate scope with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Compounds V‐1 and V‐2 have been demonstrated to be potent inhibitors of tubulin polymerization and of growth of human cancer cell lines, thus showing anti‐mitotic activity . Compounds V‐3 and V‐4 are natural products isolated from hairy root cultures of Salvia broussonetii . Compound V‐5 is biogenetically produced on oxidation of pyrogallol; its analogues compound V‐6 is natural pigments .…”
Section: Methodsmentioning
confidence: 99%
“…Compounds V‐1 and V‐2 have been demonstrated to be potent inhibitors of tubulin polymerization and of growth of human cancer cell lines, thus showing anti‐mitotic activity . Compounds V‐3 and V‐4 are natural products isolated from hairy root cultures of Salvia broussonetii . Compound V‐5 is biogenetically produced on oxidation of pyrogallol; its analogues compound V‐6 is natural pigments .…”
Section: Methodsmentioning
confidence: 99%
“…28 For instance, Meng and Cao uncovered a goldand triflic acid co-catalysed [4+2]/ring expansion domino cascade (Scheme 7). 29 Reaction of ortho-alkynylaldehyde 17 with cyclopropenes 18 in presence of 10 mol% gold catalyst and 0.5 equivalent of TfOH in dioxane at 90 1C, provided an efficient access to the corresponding benzo [7]annulene 19 in good yields, with an excellent diastereoselectivity and a complete Z-selectivity of the exocyclic olefin. The proposed mechanism suggested that, a gold-mediated 6-endo-dig cyclisation by the oxygen atom could then be followed by an endo-intermolecular Diels-Alder cycloaddition reaction with the cyclopropene 18, playing the role of the dienophile.…”
Section: Group 1: Carbon(s) Insertion Through Opening Of a Bicyclic Systemmentioning
confidence: 99%
“…A different strategy relying in a [4 + 2] cycloadditions and subsequent cyclopropane ring-opening was disclosed by Cao and co-workers (Scheme 47B). 223 Specifically, they employed ortho-alkynylbenzaldehyde derivatives 333, which served as precursors of an isochromenylium cation as 4-atom partner for the cycloaddition, and 1,2,3-trisubstituted cyclopropenes 332. This combination of reagents in the presence of a catalytic system comprising gold(III) and TfOH enable the synthesis of benzo [7]annulene derivatives 334 in moderate yields.…”
Section: Cycloaddition Reactions Of Cyclopropenes Involving Ring-clea...mentioning
confidence: 99%
“…A different strategy relying in a [4 + 2] cycloadditions and subsequent cyclopropane ring-opening was disclosed by Cao and co-workers (Scheme B) . Specifically, they employed ortho -alkynyl­benzaldehyde derivatives 333 , which served as precursors of an isochromenylium cation as 4-atom partner for the cycloaddition, and 1,2,3-trisubstituted cyclopropenes 332 .…”
Section: Cycloaddition Reactions Of Cyclopropenes Involving Ring-clea...mentioning
confidence: 99%